2015
DOI: 10.1111/codi.12923
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and quality of life after transcutaneous posterior tibial neuromodulation for faecal incontinence

Abstract: Transcutaneous posterior tibial nerve neuromodulation provides good treatment for faecal incontinence in terms of efficacy and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
2
5
0
3
Order By: Relevance
“…Posterior Tibial Nerve Stimulation (PTNS) is another option that recent studies have indicated its high effectiveness (Bondurri, Maffioli, & Danelli, 2015;de Groat & Tai, 2015;Edenfield, Amundsen, Wu, Levin, & Siddiqui, 2015;Giani & Musco 2015;Grossi et al, 2015;Gupta, Ehlert, Sirls, & Peters, 2015;Jiménez-Toscano et al, 2015;Kelly, Radley, & Brown, 2016;Lecompte, Hery, Guys, & Louis-Borrione, 2015;Lopez-Delgado et al, 2014;Marti & Maurus, 2014;Moya et al, 2016;Pena Ros et al, 2016;Sucar-Romero, Escobar-del Barco, Rodriguez-Colorado, & Gorbea-Chavez, 2014;Wexner, 2015). Although there is still an ongoing controversy regarding PTNS in FI treatment, PTNS is low cost and easy to operate without anesthesia (Hotouras et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…Posterior Tibial Nerve Stimulation (PTNS) is another option that recent studies have indicated its high effectiveness (Bondurri, Maffioli, & Danelli, 2015;de Groat & Tai, 2015;Edenfield, Amundsen, Wu, Levin, & Siddiqui, 2015;Giani & Musco 2015;Grossi et al, 2015;Gupta, Ehlert, Sirls, & Peters, 2015;Jiménez-Toscano et al, 2015;Kelly, Radley, & Brown, 2016;Lecompte, Hery, Guys, & Louis-Borrione, 2015;Lopez-Delgado et al, 2014;Marti & Maurus, 2014;Moya et al, 2016;Pena Ros et al, 2016;Sucar-Romero, Escobar-del Barco, Rodriguez-Colorado, & Gorbea-Chavez, 2014;Wexner, 2015). Although there is still an ongoing controversy regarding PTNS in FI treatment, PTNS is low cost and easy to operate without anesthesia (Hotouras et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…20 One main point in the outcome in treatment of FNRFI is the decrease in the FI severity throughout decrease the FI episodes and improvement of FI score. For the effectiveness of TPTNS, several studies 21-25 reported statistically significant improvement of FI score after 3 months or after 6 months as reported by Eleouet et al . 23 Others continued the follow-up for 12 months and reported the same results.…”
Section: Discussionmentioning
confidence: 67%
“…20 One main point in the outcome in treatment of FNRFI is the decrease in the FI severity throughout decrease the FI episodes and improvement of FI score. For the effectiveness of TPTNS, several studies [21][22][23][24][25] reported statistically significant improvement of FI score after 3 months or after 6 months as reported by Eleouet et al 23 Others continued the follow-up for 12 months and reported the same results. All of the above-reported results matched the results of the present study where there was a statistically significant improvement of the FI score at 6, 12, 24 months when compared to the baseline.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Transcutaneous tibial nerve stimulation (TTNS) targets the tibial nerve in a similar fashion to PTNS but does not require needle puncture . Compared with PTNS it is cheap, noninvasive and deliverable by the patient at home . Bilateral TTNS for functional constipation remains untested.…”
Section: Introductionmentioning
confidence: 99%